2005
DOI: 10.1097/01.opx.0000159361.17876.96
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Astigmatism and Spherical Refractive Error in a High Myopia Cohort

Abstract: In severely myopic patients, there is a high prevalence of astigmatism that is predominantly with-the-rule. The degree of myopic spherical refractive error is correlated with astigmatism severity but is not a risk factor for the presence of astigmatism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 10 publications
2
35
0
2
Order By: Relevance
“…The presence of astigmatism has been found to be associated with myopic refractive errors, that is, astigmatism was associated with higher degrees of myopia. [6][7][8][9][10]47,48 Fulton, Hansen and Petersen 6 suggested that uncorrected astigmatic errors influenced the development of myopia and that the optical blur from uncorrected astigmatism may be a trigger for myopic development. The presence and changes in astigmatism have been found by some investigators to be associated with an increased progression of myopia.…”
Section: Astigmatism and Other Refractive Errorsmentioning
confidence: 99%
“…The presence of astigmatism has been found to be associated with myopic refractive errors, that is, astigmatism was associated with higher degrees of myopia. [6][7][8][9][10]47,48 Fulton, Hansen and Petersen 6 suggested that uncorrected astigmatic errors influenced the development of myopia and that the optical blur from uncorrected astigmatism may be a trigger for myopic development. The presence and changes in astigmatism have been found by some investigators to be associated with an increased progression of myopia.…”
Section: Astigmatism and Other Refractive Errorsmentioning
confidence: 99%
“…Farbrother et al 10 in a cross sectional analysis of 19 optometric practices in the north of England, found an association between WTR astigmatism and high myopia. Heidary et al 11 completed a retrospective study of 217 severely myopic patients. They found that the degree of myopic spherical refractive error is correlated with WTR astigmatism severity.…”
mentioning
confidence: 99%
“…The presence of high astigmatism is associated with the development of amblyopia and progressive myopia [Fulton et al, 1982;Gwiazda et al, 2000]. The presence of astigmatism has also been found to be associated with higher degrees of myopia, with an increased progression of myopia by some studies [Ninn-Pedersen, 1996;Fulton et al, 1982;Gwiazda et al, 2000;Tong et al, 2002;Farbrother et al, 2004;Fan et al, 2004;Heidary et al, 2005] whereas other studies have found little to no association between the presence of astigmatism and the presence and progression of myopic refractive errors. However, there does appear to be an association between astigmatism and the development and progression of myopia [Read et al, 2007].…”
Section: Epidemiology -Prevalencementioning
confidence: 96%